Predicting noise-induced hearing loss (NIHL) in TNB workers using GDAM algorithm - Rehman Gillani, Syed Muhammad Zubair (2012)
Noise is a form of a pollutant that is terrorizing the occupational health experts for many decades due to its adverse side-effects on the workers in the industry. NoiseInduced Hearing Loss (NIHL) handicap is one out of many health hazards caused due to excessive exposure to high frequency noise emitted from the machines. A number of studies have been carried-out to find the significant factors involved in causing NIHL in industrial workers using Artificial Neural Networks (ANN). Despite providing useful information on hearing loss, these studies have neglected some important factors. The traditional Back-propagation Neural Network (BPNN) is a supervised Artificial Neural Networks (ANN) algorithm. It is widely used in solving many real time problems in world. But BPNN possesses a problem of slow convergence and network stagnancy. Previously, several modifications were suggested to improve the convergence rate of Gradient Descent Back-propagation algorithm such as careful selection of initial weights and biases, learning rate, momentum, network topology, activation function and ‘gain’ value in the activation function. This research proposed an algorithm for improving the current working performance of Back-propagation algorithm by adaptively changing the momentum value and at the same time keeping the ‘gain’ parameter fixed for all nodes in the neural network. The performance of the proposed method known as ‘Gradient Descent Method with Adaptive Momentum (GDAM)’ is compared with ‘Gradient Descent Method with Adaptive Gain (GDM-AG)’ (Nazri, 2007) and ‘Gradient Descent with Simple Momentum (GDM)’ by performing simulations on classification problems. The results show that GDAM is a better approach than previous methods with an accuracy ratio of 1.0 for classification problems like ix Thyroid disease, Heart disease, Breast Cancer, Pima Indian Diabetes, Wine Quality, Australian Credit-card approval problem and Mushroom problem. The efficiency of the proposed GDAM is further verified by means of simulations on Noise-Induced Hearing loss (NIHL) audiometric data obtained from Tenaga Nasional Berhad (TNB). The proposed GDAM shows improved prediction results on both ears and will be helpful in improving the declining health condition of industrial workers in Malaysia. At present, only few studies have emerged to predict NIHL using ANN but have failed to achieve high accuracy. The achievements made by GDAM has paved way for indicating NIHL in workers before it becomes severe and cripples him or her for life. GDAM is also helpful in educating the blue collared employees to avoid noisy environments and remedies against exposure to excessive noise can be taken in the future to prevent hearing damage.